Insects found in birds’ nests from Argentina. Part I: a bibliographical review, with taxonomical corrections, comments and a hypothetical mechanism of transmission of cimicid bugs - Turienzo, Paola; Iorio, Osvaldo Di (Zootaxa, 2007)
A bibliographical review of the insects found in birds’ nests from Argentina is herein presented. The bird species are cited as they were originally recorded in the respective publications, but their nomenclature is updated. For each kind of nest, the data are ordered in the following manner: by insect order, family, subfamily and species (references, without locality) and by province: locality with specimens when stated (reference with locality data). Comments on nomenclature and some corrections are included under the respective notes. Three items that have received most attention were the hematophagous Reduviidae: Triatominae, Cimicidae, and the larvae of Philornis (Diptera: Muscidae). Identifications of other insects are scarce, and were explicitly mentioned in only three short works, and in an anecdotal manner in other papers. In general, insects found in birds’ nests may be grouped by ecological guilds (predators, hematophagous parasitoids, detritivores, phytophagous and some predator insect hibernants, and inquilines), permanency (temporal and permanent residents) inside the nests, and according to their direct relationship to the birds. A transmission mechanism is hypothesized for the hematophagous bugs of the family Cimicidae based upon data on birds that nidificate in nests of other birds. Some new records are included.